PERUBAHAN KADAR Î² ENDORPHIN PADA PASIEN PRIMIGRAVIDA INPARTU KALA I FASE AKTIF DENGAN PENERAPAN â€œCOMFORT FOOD: SLOW-STROKE BACK MASSAGEâ€ BERBASIS TEORI KENYAMANAN KOLCABA DI RSUD KABUPATEN KEDIRI - Rahayu, Dwi; Yunarsih, Yunarsih (The Indonesian Journal of Health Science, 2016)
Pain in the first stage of labor occurs due to ischemia in uterine corpus and dilatation of the cervix (Sarwono, 2002). These sensations of pain is individual, because many factors affect, among others, the environment and cultural background (hamnah, 2003). For primiparous labor pain is a very unpleasant feeling and misery is more, because primiparous no experience and how to cope the pain (Cohen, 1991). Slow-Stroke Back Massage is an alternative therapy to reduce pain because it is easy to do. The purpose of this study is Proving ? endorphin levels through Slow-Stroke Back Massage with Comfort Theory approach in patients primigravidas Inpartu Kala I Active Phase. The study design was cross sectional with quasy Experiment Design of Post Test Only with Control Group Design. Collecting data by checking ? endorphins. Data Analysis  used statistical test Mann Whitney and obtained significant value of 0.000 means there is a difference between the control group and the treatment group. Average production of endorphins control group amounted to 7.46, and amounted to 19.54 endorphin treatment groups. Slow stroke back massage easily done by anyone and effective in terms of the economy and easy method to reduce pain intensity, it needs to be socialized.